1978
DOI: 10.1073/pnas.75.9.4538
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental ascorbate in the supportive treatment of cancer: Reevaluation of prolongation of survival times in terminal human cancer

Abstract: A study has been made of the survival times of 100 terminal cancer patients who were given supplemental ascorbate, usually 0 g/day, as part of their routine management and 1000 matched controls, similar patients who had received the same treatment except for the ascorbate. The two sets of patients were in part the same as those used in our earlier study [Cameron, E. & Pauling, L. (1976) Proc. NatL Acad. Sci. USA 73,[3685][3686][3687][3688][3689]. Tests confirm that the ascorbate-treated patients and the matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
278
2
7

Year Published

1985
1985
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 401 publications
(289 citation statements)
references
References 2 publications
2
278
2
7
Order By: Relevance
“…The benefit of high doses of ascorbate in broad-spectrum cancer treatment was initially reported by Cameron and Pauling [77]; however, subsequent trials have either shown promising benefits in certain circumstances, or have provided no detectable advantages at all [78][79][80][81][82][83][84]. Nevertheless, it remains possible that vitamin C supplementation can reverse global loss of 5hmC [6] and hypermethylation of tumor-suppressor genes [75,76].…”
Section: Reprogrammingmentioning
confidence: 98%
“…The benefit of high doses of ascorbate in broad-spectrum cancer treatment was initially reported by Cameron and Pauling [77]; however, subsequent trials have either shown promising benefits in certain circumstances, or have provided no detectable advantages at all [78][79][80][81][82][83][84]. Nevertheless, it remains possible that vitamin C supplementation can reverse global loss of 5hmC [6] and hypermethylation of tumor-suppressor genes [75,76].…”
Section: Reprogrammingmentioning
confidence: 98%
“…and oral vitamin C, usually 10 g/d, and 1,000 comparable patients not given vitamin C. Patients treated with vitamin C survived approximately four times longer than controls, with a high degree of statistical significance (P Ͻ 0.0001). A follow-up study reported that patients given vitamin C had a mean survival time almost 1 year longer than matched controls (13). Overall, 22% of vitamin C-treated patients but only 0.4% of controls survived for more than 1 year.…”
mentioning
confidence: 99%
“…The greatest proponents of vitamin C use, Linus Pauling and his collaborators, suggested benefit from high-dose (10 gm) vitamin C in terminal patients who had exhausted all conventional options [72]. A cohort of 100 ''untreatable'' cancer patients who took 10 gm of vitamin C showed a greater mean survival of 300 days and a greater number of survivors after 1 year (24% versus 0.4%) than in a historical control group of 1,000 patients.…”
Section: Antioxidantsmentioning
confidence: 99%